Thixotropic and hydration effects of Mg/Al-layered double hydroxide and sodium montmorillonite composite dispersion on oil well cement paste. (November 2022) - Li, Pengpeng; Hu, Miaomiao; Liu, Ming; Zhang, Hang; Liu, Guoqing; Xing, Yubing; Xia, Xiujian; Guo, Jintang
Abstract: Thixotropic cement paste, which destroys the grid structure under shear action and rapidly recovers its previous state after a standstill, is an effective method to solve cementing leakage and gas migration issue for oil and gas well cementing. To overcome the shortcomings of clay thixotropic agents (e.g., poor fluidity and mechanical properties with high dosage), we developed a composite nanoclay thixotropic agent (i.e., LDH/MMT) that consists of Montmorillonite (MMT) with permanent negative charges in laminates and Magnesium/Aluminum sulfate-type hydrotalcite (Mg/Al– SO 4 2 − -LDHs) with positive charges in laminates. The rheological performance of LDH/MMT and its effects on cement paste were investigated. Results showed that Mg2 Al-LDH with a high charge density of laminates significantly improved the gel strength of LDH/MMT dispersion at rest, whereas the apparent viscosity at a high shear rate was slightly affected. When mixed with cement, LDH/MMT at a low dosage endows the cement paste with high yield stress and outstanding shear thinning and thixotropic behavior by forming dynamic reversible "house of card" grid structure between cement and clay colloidal particles. Moreover, compared with neat cement paste, the increment in the compressive strength of cement pastes containing 0.3 %bwoc LDH/MMT was approximately 10% because of the pozzolanic effect and nucleation sites for the growth of hydrated calcium silicate. Highlights: Mg/Al- LDHs with different laminate charge densities were prepared. LDHs can enhance the grid structure of montmorillonite dispersion. LDH-MMT can enhance the thixotropic behavior of cement paste. LDH-MMT possesses a pozzolanic effect and acts as a nucleation site for C–S–H growth.